The Dynamic of Move in Teacher-Students’ Interaction - Aprilza Aswani (ELLITE, 2021)
The present study attempts to determine move dynamics types in teacher-student’s interaction. The research design employed in this study was qualitative content analysis. The data obtained were the form of utterances gained from teacher-student’s interaction in English classroom interaction from the second-year students of SMA Negeri 1 Tanjungbalai class XI IPA 1-3 totaling to 90 students and 3 teachers involved. The data were analyzed by following Martin’s framework of move in systemic functional linguistic theory. The findings of the study exhibit that there are three types of move dynamic found in teacher-student’s interaction namely clarification (cl)-response to clarification (rcl), confirmation (cf)-response to confirmation (rcf), and challenge (ch)-response to challenge (rch). The dynamic of move realized in the data happens due to some reasons such as the unclear information from the teacher, and the prior knowledge possessed by students. The findings imply that a teacher should consider having a dynamic interaction. This can help support the achievement of students’ success in the teaching-learning process. The dynamic of interactions in the form of clarification, confirmation, and challenge shows that students follow and comprehend the meaning uttered by student.